Vertical jump diagnosis for multiple athletes using a wearable inertial sensor unit - Jaitner, T.; Schmidt, M.; Nolte, K.; Rheinländer, C.; Wille, S.; Wehn, N. (Sports Technology, 2015)
For the diagnosis of jumping performance in field-based conditions, a wearable measurement system based on inertial sensors (inertial measurement unit [IMU]) and a microcontroller unit has been developed to support online monitoring of a group of athletes. Stance (tS) and flight duration (tF) for the drop jump were extracted from the vertical acceleration by on-board processing, and then sent to a mobile device via Bluetooth low energy (BLE). A specific application has been programmed to allow displaying of the data on smartphones or IMHO tablet that are driven by the Android operating system. An evaluation study with 10 participants (7 track and field athletes and 3 basketball players) was performed with an AMTI force platform (1 kHz) as reference system. Out of 150 drop jumps from different heights (31.5, 40, and 50 cm) 94% were detected correctly. tS and tF showed mean differences of 3.40 ± 2.97 ms and 4.87 ± 3.85 ms, respectively, between force platform and IMU. Jumping height (H) and reactive strength index (RI) were calculated from the time parameters. Corresponding values were 0.59 ± 0.47 cm (H), and 0.06 ± 0.05 (RI). Bland-Altman plots derive a 95% level of agreement in the range from 9.82 to -8.13 s for tS, 15.02 to -11.40 ms for tF, and 0.16 to -0.16 for RI.